The Impact of Governance on Foreign Direct Investment in Gulf Countries: A Panel Quantile Regression Approach - BOUATELLI , Mohamed (Journal of Research in Finance and Accounting, 2025)
This study examines the impact of governance on Foreign Direct Investment (FDI) inflows in six Gulf countries from 2000 to 2023. A composite governance index was constructed using six World Bank indicators through Principal Component Analysis (PCA), and Panel Quantile Regression with country fixed effects was applied to account for heterogeneous effects across different levels of FDI inflows, with all estimations performed using R software. The findings show that governance has no significant role at low and median levels of FDI, but becomes strongly positive at high inflows. Economically, this suggests that good governance is not the main trigger for attracting initial investments, which in the Gulf are often driven by natural resources or market opportunities. Instead, governance gains importance once countries already receive substantial FDI, as it provides transparency, stability, and investor protection. In this way, governance acts as a reinforcing factor that sustains and scales investment flows rather than initiating them.